Somatotrophic and thyroid hormones around the onset of lay in broiler breeders under different conditions - Malheiros, R. D.; Moraes, V. M. B.; Furlan, R. L.; Bruggeman, V.; Buyse, J.; Decuypere, E.; Macari, Marcos [UNESP] (Akademiai Kiado, 2002)
Somatotrophic and thyroid hormones were determined around the onset of reproduction in broiler breeders reared in two different housing systems [dark, close-sided house (CH) and conventional, open-sided house (OH)]. In both groups age-related changes were obvious for thyroxine (T-4), growth hormone (GH) and insulin-like growth factor (IGF-1); levels of T-4 decreased, especially between 24 and 28 weeks in both groups; concomitantly GH sharply increased over the same period. A transient peak in triiodothyronine (T-3) occurred between 25 and 27 weeks. The effect of housing was only present after the onset of lay. Between weeks 27-28 and the end of the period studied, the CH group showed higher levels of GH and T-3 but lower T-4 levels as compared to the OH group. A significant increase in GH after onset of lay, without any significant rise in T-3 or in IGF-I, could point to a relative insensitivity to high plasma GH levels. Changes at GH receptor level, together with an increased pituitary GH secretion and/or decreased GH turnover may be expected. This may indicate that hypothalamo-pituitary changes at the onset of lay not only imply changes of gonadotrophic cell function, but also other hormonal axes. The relatively decrease in T-4 without changes in T-3, may point to a decrease in the activity of the thyrotropic axis.
Keywords: Hormones; broiler breeders; reproduction; Environment; Growth hormone; thyroid hormones